2001
DOI: 10.1515/cclm.2001.089
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Sequential Measurements of Cancer Antigen 125 (CA 125), Carcinoembryonic Antigen (CEA) and Tissue Polypeptide Antigen (TPA) Based on Analytical Imprecision and Biological Variation in the Monitoring of Ovarian Cancer

Abstract: The main objective with cancer antigen 125 (CA 125), carcinoembryonic antigen (CEA), and tissue polypeptide antigen (TPA) monitoring of ovarian cancer patients is to detect an early change of disease activity with high reliability. We hypothesized that a monitoring scheme for ovarian cancer patients with serological tumor markers should take into account the stochastic variation, i.e. the probability that observed increases and decreases may solely be due to analytical imprecision and normal intra-individual b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The CV w values for CA 125 and CEA in this study were similar to those reported previously (15)(16)(17). The components of BV for CYFRA 21-1 in healthy individuals are unknown (15 ).…”
supporting
confidence: 89%
“…The CV w values for CA 125 and CEA in this study were similar to those reported previously (15)(16)(17). The components of BV for CYFRA 21-1 in healthy individuals are unknown (15 ).…”
supporting
confidence: 89%
“…2 Within the last decade, discussions about normal and ln-normal distributions of biological parameters have become intense and the tendency is now moving towards the application of ln-distributions. [4][5][6][7][8] One problem with the RCV is that it can only be used in assessment of differences between two serial results, which makes it susceptible to the effect of repeated testing, where the probability of false-positive results increases with the number of results available. Therefore, a new concept to overcome the problems with repeated testing, by keeping the probability of false-positive results constant for several consecutive results and only dependent on the number of results available seems worthwhile.…”
Section: Number Of Results (N)mentioning
confidence: 99%
“…These results may be extended to other settings, where the lognormal approach was recognized to make a better use of data distribution when assessing biological variation. This was shown by Tuxen et al [16] for cancer antigen 125 (CA 125), carcinoembryonic antigen (CEA), and tissue polypeptide antigen (TPA) in the monitoring of ovarian cancer patients or by van Eyben et al [17] for serum lactate dehydrogenase isoenzyme1 (S-LD-1) in the monitoring of patients with testicular germ cell tumors.…”
Section: Discussionmentioning
confidence: 96%
“…As component of variation is computed based on nANOVA, the distributional assumptions underlying the use of this method should be satisfied, which is not the case for skewed distributions, as NT-proBNP's. This aspect has been underlined in the literature not only for NTproBNP, but also for other biomarkers in oncologic research [16,17]. Particularly, Fokkema et al [18] showed that the deviation of the mean from the median of week to week measurements was much larger (by a factor of 20) before log-transformation of NT-proBNP concentrations.…”
Section: Introductionmentioning
confidence: 96%